Uma avaliação do impacto do treinamento na produtividade do trabalho. - Mello, Luciana Heringer Freitas de (2009)
The present study aimed to verify the training involved in labor productivity. The theoretical framework was based on Training, Levels of Education, Qualification and Productivity. The methodological process, based on structuralism, sought to identify and describe the underlying relationships between training and productivity in its essential elements. The study is exploratory, descriptive and explanatory. Data collection was conducted through semi-structured interviews, using saturation criterion to define the number of interviews. Managers and professionals of three large corporations placed in Rio de Janeiro were interviewed, trying to identify the relationship between labor productivity and training management. To analyze the data an array was built containing the answers of the respondents who supported the interpretation of information. The results indicate that it is not possible to establish a direct co-relation between training and labor productivity in the group studied, because: 1) training is carried out based on considerations of several areas of productivity (update techniques, assimilation, competition, maximization of performance); 2) labor productivity is rarely measured, often not even controlled; and 3) there is a conceptual confusion between performance (effort made) and productivity (result achieved).